Analysis of Electromagnetic Interference Effects of 5G Signals on Radio Altimeters - Zhaobin Duan; Ke Xu; Zhenyang Ma; Peng Wang (Aerospace)
An analytical method is introduced to assess the susceptibility of radio altimeter (RA) receivers to adjacent-band fifth-generation (5G) signal interference and to quantify its impact on RA performance. The power-series method is employed to analyze the intermediate frequency (IF) signal gain compression effect of 5G signal interference on RA receivers. A behavioral-level simulation model of the RA receiver’s radio frequency (RF) front-end is constructed based on the advanced design system (ADS), and a 5G signal injection simulation is performed. The simulation results indicate that 5G signals can induce nonlinear effects in the RF front-end circuit of the RA, leading to IF signal gain compression, thereby affecting the subsequent signal processing of RA receivers. The interference effect on the RA receiver is influenced by factors such as the power and frequency of the 5G interference signal. To investigate this, an interference injection test was conducted on a specific RA receiver to validate the aforementioned interference mechanisms. The test results indicate that when the average power of the injected 5G signal at a frequency of 4000 MHz reaches −16 dBm, the IF signal power is significantly reduced. As the power of the 5G signal increases, this nonlinear effect becomes more pronounced. Furthermore, the height error ratio significantly increases, with consistent trends observed across different test frequencies. The interference threshold for the RA is lower when the signal frequency is closer to the RA operational signal frequency. Our research results demonstrate the efficacy of this method, providing a reference basis for studies on interference mechanisms and the evaluation of interference effects related to RA receivers within the electromagnetic environment of 5G signals.